The Effect of Macroeconomic and Internal Bank Factors on Distribution of Sharia Banking Mortgage in Indonesia - Rani, Lina Nugraha; Varizqa, Adella Dwita (International Journal of Islamic Economics and Finance (IJIEF), 2025)
Sharia mortgage financing growth in Indonesia is shaped by both macroeconomic conditions and internal banking performance. This study aims to examine the influence of macroeconomic variables, Industrial Production Index, inflation, BI rate and internal bank factors, Third-Party Funds, Non-Performing Financing of Sharia mortgages, and total assets on the distribution of Sharia mortgage financing in Indonesia. The research employs the Autoregressive Distributed Lag method. The results indicate that in the short term, all variables have a significant effect on Sharia mortgage financing. Industrial Production Index, inflation, Third-Party Funds, mortgage Non-Performing Financing, and total assets have a significant positive impact, while the BI rate has a significant negative effect. In the long term, only IPI and mortgage Non-Performing Financing show a significant positive influence on the distribution of Sharia mortgage financing. Inflation, the BI rate, and total assets have a positive but insignificant effect, while Third-Party Funds has a negative and insignificant effect. This study suggests that the government should implement appropriate macroeconomic policies, and Islamic banks should consistently maintain internal banking factors to optimize the distribution of Sharia mortgage financing. This will facilitate home ownership through Sharia mortgages and contribute to strengthening Indonesia’s economy, as the housing sector plays a strategic role with its capital and labour-intensive industries